Model for Proton Acceleration in Strongly Self-Magnetized Sheath Produced by Ultra-High-Intensity Sub-Picosecond Laser Pulses - Artem V. Korzhimanov (Quantum Beam Science)
Recently, it has been experimentally shown that the sheath acceleration of protons from ultra-thin metal targets irradiated by sub-picosecond laser pulses of intensities above <semantics>1021</semantics> W/cm2 is suppressed compared to well-established models. This detrimental effect has been attributed to a self-generation of gigagauss-level quasi-static magnetic fields in expanded plasmas on the rear side of a target. Here we present a set of numerical simulations which support this statement. Based on 2D full-scale PIC simulations, it is shown that the scaling of a cutoff energy of the accelerated protons with intensity deviates from a well-established Mora model for laser pulses with a duration exceeding 500 fs. This deviation is showed to be connected to effective magnetization of the hottest electrons producing at the maximum of the laser pulse intensity. We propose a modification of the Mora model which incorporates the effect of the possible electron magnetization. Comparing it to the simulation results shows that by appropriately choosing a single fitting parameter, the model produces results that quantitatively coincide with simulations.